Kinetic shading devices for multi-storey office buidlings in the tropics - Lee, Siew Jing (2022)
In tropical climate regions, daylighting is abundant but is not fully utilized in building design due to the undesirable solar heat gain. Shading systems are crucial in building design particularly for multi-storey office buildings in the tropics. However, the internal daylighting level in office buildings of Malaysia was insufficient due to the improper use of fixed shading devices. Kinetic shading systems are capable to improve the quality and quantity of daylighting in multi-storey office buildings in the tropics as the kinetic shading devices can respond to the dynamic sky condition. The objectives of the study is to identify the factors that would affect the performance of kinetic shading device of multi-storey office building in the tropics, to implement a kinetic shading system that interacts with the dynamic sky conditions and to improve the daylighting performance of the workplace with providing optimum indoor illuminance level. The methodology used in this study is mixed method research. Literature review and case studies contributed to the design parameters of kinetic shading devices by observation and comparison. Six types of shading devices are proposed and being assessed through the daylighting analysis simulation. An experiment is conducted using Velux Daylight Visualizer and SketchUp. The daylighting performance of the proposed shading devices are assessed through the computer simulation software, Velux Daylight Visualizer. The findings identified the kinetic shading devices which could provide optimum daylighting performance at each orientation and times under tropical sky. This study contributes to the exploration of kinetic shading devices design and the implementation of kinetic shading devices on office buildings in the tropics. Nevertheless, further studies are needed to consider the energy consumption of kinetic shading systems and daylighting performance analysis using real climate data.